PENGARUH TEKNIK RELAKSASI NAFAS DALAM DAN AROMATERAPI LAVENDER UNTUK PENURUNAN TINGKAT KECEMASAN PASIEN PRE OPERASI APENDIKSITIS - Nurdin, Ria Oktasari; Dahrizal, Sariman Pardosi, (JURNAL MEDIA KESEHATAN, 2018)
The surgical procedure gives reactions such as fear, anger, anxiety and anxiety. Anxiety is anormal phenomenon in new experiences and things that have not been tried. The magnitude of anxietydepends on the expected outcome of the surgery, the benefits and the type of organ being removed.This research is to know the effect of breath relaxation technique in using lavender aromatherapy todecrease the anxiety level of pre surgical patient appendiksitis in RSUD Dr. M.Yunus Bengkulu.Research using Pre-experimental with one-group pretest-posttest design. The sample was appendixitispatients totaling 20 people taken by accidental sampling. Data analysis with paired t test. The datashowed averages before the intervention anxiety value 28.70 and after intervention 23.70. There isdifference of anxiety value after intervention (p = 0,001 ≤ α 5% meaning, there is decrease of anxietyvalue before and after intervention. Conclusions and Suggestions: The nurse provides information andasks the family to provide lavender aromatherapy as a preparation for surgery to reduce preoperativepatient anxiety.